Molecular mechanisms of thalidomide and its derivatives - ITO, Takumi; HANDA, Hiroshi (Proceedings of the Japan Academy, Series B, 2020)
Thalidomide, originally developed as a sedative drug, causes multiple defects due to severe teratogenicity, but it has been re-purposed for treating multiple myeloma, and derivatives such as lenalidomide and pomalidomide have been developed for treating blood cancers. Although the molecular mechanisms of thalidomide and its derivatives remained poorly understood until recently, we identified cereblon (CRBN), a primary direct target of thalidomide, using ferrite glycidyl methacrylate (FG) beads. CRBN is a ligand-dependent substrate receptor of the E3 ubiquitin ligase complex cullin-RING ligase 4 (CRL4CRBN). When a ligand such as thalidomide binds to CRBN, it recognizes various ‘neosubstrates’ depending on the shape of the ligand. CRL4CRBN binds many neosubstrates in the presence of various ligands. CRBN has been utilized in a novel protein knockdown technology named proteolysis targeting chimeras (PROTACs). Heterobifunctional molecules such as dBET1 are being developed to specifically degrade proteins of interest. Herein, we review recent advances in CRBN research.